The rehabilitation of stroke patients at community health centres in the Western Cape - A. Rhoda; R. Mpofu; W. DeWeerdt (AOSIS, 2009)
The structure and process of rehabilitation of stroke patientsaffects the outcomes of the patients. The aim of this study was to determine thestructure and process of rehabilitation of stroke patients at Community HealthCentres  (CHCs) in the Western Cape, South A frica. A  quantitative descriptive study was conducted. Questionnaires and archived records were used to collect the data. The study sample used to collect information related to the structure consisted of therapists (16) employed at the centres; while the study sample used to collect information related to the process consisted of 100 first time stroke patients. Descriptive statistics were conducted using Excel and SPSS. The results of the study revealed that there is a lack of occupational and speech therapy services at the centres forming partof the study sample. At centres where these services are provided the frequency and intensity with which the services are received by the patients is extremely low. Further research is needed to determine if the decreased intensity is onlyas a result of decreased availability of services or if inability of stroke clients to access the services also plays a role.